Role of branding in Indian hospitals - SUBRAHMANYAM, CHALLA MARUTHY; SATPATHY, DR SARITA; SATPATHY, DR S. K (The journal of contemporary issues in business and government, 2021)
Indian hospitals are using branding to create a positive outlook about their services to outpatient. This in turn enhances outpatient confidence on the hospital, increases loyalty and chances for revisiting hospital. Branding also helps the hospital to stand out from competition. The whole branding activities will lead to increase in revenue. Among the hospitals, private hospitals are seen to adopt branding more. Messages reflecting brand communication can be seen on print media, electronic media, display boards inside hospital premises and hoardings. Branding influences some factors. Awareness of these factors will help hospitals to plan their branding activities better. Hospitals can focus on factors having influence from branding and can drop or reduce focus on factors that do not have influence by branding. The purpose of this study is to identifying factors that are influenced by branding. Data on the 13 factors is collected by an online questionnaire on 429 outpatients. Chi square test was performed to find the association of factor with hospital branding. 12 factors showed statistically significant association with branding indicating that branding does affect those 12 factors. The option having the highest frequency of respondents amongst 7 options was identified for all the 12 factors. This option is concluded as having the maximum influence by hospital branding. Only 1 factor did not show statistically significant association with hospital branding.